Denosumab in patients with aneurysmal bone cysts: A case series with preliminary results. Issue 5 (October 2018) - Palmerini, Emanuela; Ruggieri, Pietro; Angelini, Andrea; Boriani, Stefano; Campanacci, Domenico; Milano, Giuseppe M.; Cesari, Marilena; Paioli, Anna; Longhi, Alessandra; Abate, Massimo E.; Scoccianti, Guido; Terzi, Silvia; et al.
Purpose: Aneurysmal bone cyst (ABC) is a rare skeletal tumor usually treated with surgery/embolization. We hypothesized that owing to similarities with giant cell tumor of bone (GCTB), denosumab was active also in ABC. Methods: In this observational study, a retrospective analysis of ABC patients treated with denosumab was performed. Patients underwent radiologic disease assessment every 3 months. Symptoms and adverse events were noted. Results: Nine patients were identified (6 male, 3 female), with a median age of 17 years (range 14–42 years). Primary sites were 6 spine–pelvis, 1 ulna, 1 tibia, and 1 humerus. Patients were followed for a median time of 23 months (range 3–55 months). Patients received a median of 8 denosumab administrations (range 3–61). All symptomatic patients had pain relief and 1 had paresthesia improvement. Signs of denosumab activity were observed after 3 to 6 months of administration: bone formation by computed tomography scan was demonstrated in all patients and magnetic resonance imaging gadolinium contrast media decrease was observed in 7/9 patients. Adverse events were negligible. At last follow-up, all patients were progression-free: 5 still on denosumab treatment, 2 off denosumab were disease-free 11 and 17 months after surgery, and the last 2 patients reported no progression 12 and 24 months after denosumab interruption and no surgery. Conclusions: Denosumab has substantial activity in ABCs, with favorable toxicity profile. We strongly support the use of surgery and/or embolization for the treatment of ABC, but denosumab could have a role as a therapeutic option in patients with uncontrollable, locally destructive, or recurrent disease.